A New Wearable System for Personal Air Pollution Exposure Estimation: Pilot Observational Study - Sara Bernasconi; Alessandra Angelucci; Andrea Rossi; Andrea Aliverti (JMIR mHealth and uHealth, 2025)
Abstract BackgroundAir pollution is a major environmental cause of premature deaths, responsible for around 7 million deaths annually. In this context, personal air pollution exposure (PAPE), the product of pollutant concentration and minute ventilation (V’mV’m ObjectiveThis study evaluates the feasibility of using a wearable body sensor network (BSN) to estimate PAPE in real-life settings, assess its capability to detect spatiotemporal variations in pollution levels, and compare inhaled dose estimates from the BSN with those from fixed monitoring stations and standard V’m MethodsThe system, a BSN capturing physiological (pulse rate [PR] and respiratory rate [RR]) and environmental data, including health-affecting pollutants (particulate matter [PM] 1, PM2.5, PM10, CO22V’m ResultsVariations in RR were found among volunteers and at different locations for the same participant. Significant differences (P22V’mPrP ConclusionsThe BSN provides high-resolution spatiotemporal data on personal exposure, capturing differences in pollution levels dependent on time, location, and surrounding environment, along with individual physiological variations. It offers a more accurate estimation of inhaled dose in real-life settings, supporting personalized exposure assessments and potential applications in activity planning and complementing epidemiological research.